A Chemical Library Approach to Organic-Modified Peptide Ligands for PDZ Domain Proteins: A Synthetic, Thermodynamic and Structural Investigation - Udugamasooriya, D. Gomika (2008)
PDZ domains are members of the protein interaction domain family,[1] semi-autonomous modules embedded within larger signaling proteins that impart a degree of exclusivity to the binding properties of their hosts. As mediators of mammalian protein-protein interactions that number in the hundreds, PDZ domains are party to a correspondingly large array of cellular processes, most notably those that regulate or support neuronal activities.[2] Specific, bioavailable molecular probes are needed to foster biological inquiries into their functions; towards this end, we report our recent progress in the discovery and development of PDZ domain inhibitors.